A case-crossover study of work-related acute traumatic hand injuries in the People’s Republic of China - Jin, Kezhi; Lombardi, David A.; Courtney, Theodore K.; Sorock, Gary S.; Li, Mingqiang; Pan, Rong; Wang, Xiaorong; Lin, Joyce; Liang, Yan; Perry, Melissa J. (Scandinavian Journal of Work, Environment & Health, 2012)
' ' OBJECTIVE ': 'The aim of this study was to quantify potential transient risk factors for occupational acute hand injury among hospitalized workers in the People’s Republic of China (PRC). ' ' METHODS ': 'Participants were recruited from 11 medical facilities in 3 cities of the PRC. A face-to-face interview was used to collect information on the occurrence of 8 potential risk factors within a 90-minute time period before an acute traumatic hand injury and during a control period within the month before the injury. The reliability of reporting transient risk factors was assessed, and a case-crossover design was used to estimate the injury incidence risk ratio (IRR) of each risk factor. ' ' RESULTS ': 'In total,703 hospitalized workers completed the interview (527 male, 176 female), with a mean age of 31.8 [standard deviation (SD) 10.3] years. The median time interval between injury and interview was four days. Thirty percent of participants had a crush injury and 25.7% had an amputation. Using malfunctioning machinery/tools/material, performing a task with a different method, working overtime, and wearing gloves were found to have good reliability in test-retest examination [intra-class correlation coefficient (ICC)>0.9]. The IRR of a hand injury were markedly increased while using malfunctioning machinery/tools/material [110.4, 95% confidence interval (95% CI) 97.4–125.2], performing a task with a different method than usual (84.3, 95% CI 67.7–105.1), or being distracted (69.6, 95% CI 57.9–83.7). Gender and size of company were associated with differences in glove usage. ' ' CONCLUSIONS ': 'The results suggest the importance of transient, potentially modifiable factors in the etiology of occupational acute hand injury in the PRC. Regular maintenance of machinery/tools, work practice controls, and avoiding distractions should be priorities for reducing the risk of occupational acute hand injuries.
Keywords: acute traumatic hand injury; case-crossover study; China; hand injury; hospitalization; occupational injury epidemiology; People Republic of China; relative risk; reliability; transient risk factor